Pengembangan Pembelajaran Menulis Teks Ceramah Dengan Model Problem Based Learning Dipadukan Media Gambar Pada Siswa Kelas XI SMA - Lia Kumala Sari; Mohammad Siddik; Widyatmike G. Mulawarman (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2019)
Writing entitled Development of Text Writing Lesson Lecture with Problem Based Learning Model Combined Image Media for Students Class XI on High School aims to examine the development of learning text writing lecture with Problem Based Learning (PBL) learning model with the help of picture media in grade XI high school students. The scope of this development is limited only to planning, materials and evaluation in the learning process. The method used in this research is Research and Development (R & D), using development research design with ADDIE model, ie Analysis (stage), Design (Design) stage, Development stage, Implementation stage and Evaluation stage (evaluation). Source of data that became the object in this research is the students of class XI in SMA Negeri 8 PPU. The results of development are obtained based on two aspects: feasibility, practicality and effectiveness. So that data obtained the feasibility of 71%, practicality is 84%, 83% effectiveness. Overall the quality of teaching materials that are the product of this development is categorized as appropriate for the use of odd semester class XI students. The benefits of this development for Indonesian language teachers are expected to help as an alternative choice of text lecture lessons. For students, this development model can make students more creative, innovative, more productive. For the author itself is expected to be a means to deepen science. In addition, it is hoped that the results of development will be useful for the school as a useful source of information for the development of Indonesian language learning model.